ABE-IBS based signature-encryption method for WSN - QI Zheng-hua; YANG Geng; REN Xun-yi; WANG Hui (Tongxin xuebao)
In order to improve the security and efficiency performance of wireless sensor network signature-encryption,on the basis of identity-based signature（IBS） with the bilinear pairings on elliptic curves,an attribute-based encryption combined with identity-based signature （ABE-IBS） scheme was proposed,besides,one efficient signature-encryption scheme for WSN was also discussed. Analysis and experimental results show that proposed scheme has the low complexity and storage requirement,and can enhance the security of wireless sensor network.